Correction: Two-year field testing of genetically engineered American chestnut reveals fungal blight tolerance - Thomas Klak; Steven E. Travis; Virginia Grace May; Ek Han Tan; Matthew W. H. Chatfield; Miranda Wheeler (New Forests, 2026)

Two-year field testing of genetically engineered American chestnut reveals fungal blight tolerance - Thomas Klak; Steven E. Travis; Virginia Grace May; Ek Han Tan; Matthew W. H. Chatfield; Miranda Wheeler (New Forests, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Salmonids in hot water: An unprecedented warm‐water event in Labrador, a subarctic region of Canada - Emilie A. Geissinger; Travis E. Van Leeuwen; Nicholas Kelly; Curtis Pennell; Michelle G. Fitzsimmons; Steven Duffy; Rebecca Poole; Joey Angnatok; J. Brian Dempson; David Coté (Fisheries Management and Ecology, 2024)
Unprecedented warm river temperatures in July 2023 in Labrador, a subarctic region of Canada, were the highest since monitoring began (1994–2023) and ranged from 19.4°C (Hunt River) to 22.5°C (Eagle River). Incipient lethal water temperatures were exceeded for adult Atlantic salmon and brook trout (≥25°C) on 14 days in five of seven rivers and Arctic charr (≥24°C) on 17 days in six of seven rivers. Consequently, Labrador had the greatest number of angling restrictions and closures in 2023. Recent warming serves as a warning to fishery managers of regions historically unaffected by heat waves of the need to prepare action plans that mitigate the effects of a warming climate on fishes.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Capacity contributions of Southern Oregon offshore wind to the Pacific Northwest and California - Travis C. Douville; Steven Zhou; Jinxiang Zhu; Mark Severy (The Electricity Journal, 2024)

Can the marsh migrate? Factors influencing the growth of Spartina patens under upland conditions - Tessa M. Dowling; Steven E. Travis; Pamela A. Morgan; Gregory P. Zogg (Wetlands Ecology and Management, 2023)
The high elevation salt marsh plant Spartina patens can potentially cope with accelerated sea level rise by migrating inland, but the ability to do so may differ among plant ecotypes. We compared performance among ecotypes collected from three different sites within mesocosms in which we manipulated soil type, plant litter and salinity. Half of our treatment levels simulated conditions plants would encounter when expanding into terrestrial environments (i.e., upland soil, litter present and low salinity); the other half expansion into tidal creeks (i.e., marsh soil, litter absent, and high salinity). Plant litter and salinity did not significantly affect aboveground biomass or rhizome growth and only affected flowering in a three-way interaction with site. However, all three parameters were significantly affected by soil conditions and the site × soil interaction. Upland soil conditions reduced aboveground biomass, rhizome growth and flowering, as compared to marsh soil conditions, for ecotypes from some sites but not others. When just comparing plant performance in the upland soil treatment, ecotypes from some collection sites did better than others. One plausible explanation for this ecotypic variation is pre-adaptation to differences we found in organic matter content among our collection sites, with the ecotype collected from the site with the lowest organic matter content generally being least impacted by upland soil conditions. Our results indicate that S. patens ecotypes can vary in their capacity to successfully expand into uplands, and thus we suggest prioritizing conservation of such ecotypes, as well as their use in restoration efforts. Consideration of ecotypic variation might also prove useful in deciding where to focus conservation efforts for marsh migration.

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Long‐term patterns in inland fish kills associated with cold‐shock and winter stress: a regional case study from Texas - Steven G. Lopez; Andrea S. Aspbury; Sarah R. Fritts; Travis Tidwell; Timothy H. Bonner (Journal of Fish Biology, 2023)
Colder water temperatures are generally regarded as a stressful period for fishes ( i.e. , winter stress syndrome), which can be exacerbated by cold‐shock stress associated with major arctic freezes. Although cold‐shock stress and mass mortalities are well documented for coastal marine fishes, few studies report the effects of winter stress or cold‐shock stress on inland fishes. The purposes of this study were to describe patterns in inland fish mortalities associated with winter stress syndrome and with cold‐shock stress in Texas as a regional example of inland fish mortalities associated with colder water temperatures. Using fish mortality reports (1969–2021) recorded by state agency biologists, colder water temperature mortalities occurred in 66% ( N = 35) of the years, with greatest percentages of the reports occurring during three major arctic freezes in 1981, 1983 and 2021. The majority of reports were from urbanized counties (79%) and from lentic habitats (56%). Seventeen taxa and 1,021,217 individuals were estimated to be killed during the 53s years. Numbers of inland fish mortalities were greater during major arctic freeze years than non‐major arctic freeze years, attributed primarily to mortalities of non‐native fishes ( e.g., blue tilapia Oreochromis aureus , suckermouth catfish Hypostomus plecostomus ). Numbers of native fish mortalities, primarily clupeids and catostomids, were not different between major arctic freeze years and non‐major arctic freezes. The 43,000 inland fish mortalities reported during major arctic freeze years are in stark contrast to the 35 million coastal marine fish mortalities. Proposed mechanisms to explain cold‐shock mortalities in coastal waters ( e.g., species within the northern extent of their range, lack of access to deeper water) are similar in inland waters, yet inland waters do not have the same level of mortalities. Consequently, the disparities between mortalities in coastal and inland waters are not readily discernable at this time.

Mechanism of astatine and bismuth sorption on extraction chromatography resins from nitric acid media - Evgeny E. Tereshatov; Jonathan D. Burns; Steven J. Schultz; Brooklyn D. Green; Gabriela A. Picayo; Laura A. McCann; Lauren A. McIntosh; Gabriel C. Tabacaru; Austin Abbott; Matthew Berko; Emily Engelthaler; Kris Hagel; et al. (Chemical Engineering Journal, 2023)

Snowmelt estimation using an empirical radiation model - Steven F. Daly; Jeremy Giovando; Daniel Hamill; Travis Dahl; Michael Bartles (Journal of Hydrology, 2023)

Tissue Distribution of Mercury in the Bodies of Wild American Alligators (Alligator mississippiensis) from a Coastal Marsh in Louisiana (USA) - Liberty A. Moore; John W. Finger; David L. Haskins; Ruth M. Elsey; Steven B. Castleberry; Travis C. Glenn; Charles H. Jagoe; I. Lehr Brisbin (Archives of Environmental Contamination and Toxicology, 2022)

Genotypic Diversity Reduces the Negative Effects of Increased Competition, Herbivory, and Tidal Inundation on the Productivity of Spartina alterniflora - Gregory P. Zogg; Steven E. Travis (Estuaries and Coasts, 2022)

Distributions of native and invasive Typha (cattail) throughout the Prairie Pothole Region of North America - Brian A. Tangen; Sheel Bansal; Joanna R. Freeland; Steven E. Travis; Jennifer D. Wasko; Terence P. McGonigle; L. Gordon Goldsborough; Keira Gow; Joy E. Marburger; Jacob A. Meier (Wetlands Ecology and Management, 2022)

Predicting how climate change threatens the prey base of Arctic marine predators - Katie R. N. Florko; Travis C. Tai; William W. L. Cheung; Steven H. Ferguson; U. Rashid Sumaila; David J. Yurkowski; Marie Auger‐Méthé (Ecology Letters, 2021)
Arctic sea ice loss has direct consequences for predators. Climate‐driven distribution shifts of native and invasive prey species may exacerbate these consequences. We assessed potential changes by modelling the prey base of a widely distributed Arctic predator (ringed seal; Pusa hispida ) in a sentinel area for change (Hudson Bay) under high‐ and low‐greenhouse gas emission scenarios from 1950 to 2100. All changes were relatively negligible under the low‐emission scenario, but under the high‐emission scenario, we projected a 50% decline in the abundance of the well‐distributed, ice‐adapted and energy‐rich Arctic cod ( Boreogadus saida ) and an increase in the abundance of smaller temperate‐associated fish in southern and coastal areas. Furthermore, our model predicted that all fish species declined in mean body size, but a 29% increase in total prey biomass. Declines in energy‐rich prey and restrictions in their spatial range are likely to have cascading effects on Arctic predators.

Identifying Policy-relevant Indicators for Assessing Landscape Vegetation Patterns to Inform Planning and Management on Multiple-use Public Lands - Sarah K. Carter; L. E. Burris; Christopher T. Domschke; Steven L. Garman; Travis Haby; Benjamin R. Harms; E. Kachergis; S. E. Litschert; Kevin H. Miller (Environmental Management, 2021)
Understanding the structure and composition of landscapes can empower agencies to effectively manage public lands for multiple uses while sustaining land health. Many landscape metrics exist, but they are not often used in public land decision-making. Our objectives were to (1) develop and (2) apply a process for identifying a core set of indicators that public land managers can use to understand landscape-level resource patterns on and around public lands. We first developed a process for identifying indicators that are grounded in policy, feasible to quantify using existing data and resources, and useful for managers. We surveyed landscape monitoring efforts by other agencies, gathered science and agency input on monitoring goals, and quantified the prevalence of potential indicators in agency land health standards to identify five landscape indicators: amount, distribution, patch size, structural connectivity, and diversity of vegetation types. We then conducted pilot applications in four bureau of land management (BLM) field offices in Arizona, California, and Colorado to refine procedures for quantifying the indicators and assess the utility of the indicators for managers. Results highlighted the dominance of upland and the limited extent of riparian/wetland vegetation communities, moderate connectivity of priority vegetation patches, and lower diversity of native vegetation types on BLM compared to non-BLM lands. Agency staff can use the indicators to inform the development of quantitative resource management objectives in land use plans, evaluate progress in meeting those objectives, quantify potential impacts of proposed actions, and as a foundation for an all-lands approach to landscape-level management across public lands.

Strandings provide insight into social group structure of Atlantic white‐sided dolphins - Katie R. Pugliares‐Bonner; Kate LaSpina; Kathryn S. Rose; Steven E. Travis; Kristina M. Cammen (Marine Mammal Science, 2021)
Atlantic white‐sided dolphins ( Lagenorhynchus acutus ) are highly social odontocetes with a poorly understood tendency to mass strand. With limited capacity to study social ecology in the open ocean, mass strandings provide an opportunity to improve our understanding of group structure. Our study of 32 mass stranding events that occurred on Cape Cod, Massachusetts, between 1999 and 2009 identifies aspects of social ecology that vary across the year. A greater number of mass stranding events occurred outside of the breeding season and there was evidence of age‐structuring during the breeding season. We find generally low average intragroup pairwise relatedness assessed across eight microsatellite loci in a subset of 16 mass stranding events. Mass stranded groups do not show higher than expected relatedness when compared to a baseline estimate derived from single‐stranded individuals. Overall, our integration of genetic estimates of relatedness with data on sex and maturity‐class from stranded specimens suggests that Atlantic white‐sided dolphins fall near the more fluid end of the continuum from short‐term, highly fluid social associations to long‐term, stable groups represented among the odontocetes. Despite their tendency to mass strand, stable, kin‐based associations are not a defining feature of social group structure in this species.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

The experimental range extension of guppies (Poecilia reticulata) influences the metabolic activity of tropical streams - Antoine O. H. C. Leduc; Steven A. Thomas; Ronald D. Bassar; Andrés López-Sepulcre; Keeley MacNeill; Rana El-Sabaawi; David N. Reznick; Alexander S. Flecker; Joseph Travis (Oecologia, 2021)

Projected effects of climate change on the distribution and abundance of breeding waterfowl in Eastern Canada - Antoine Adde; Diana Stralberg; Travis Logan; Christine Lepage; Steven Cumming; Marcel Darveau (Climatic Change, 2020)

Correction to: Niche Partitioning among Snook (Pisces: Centropomidae) in Rivers of Southeastern Florida and Implications for Species Range Limits - Philip W. Stevens; Jynessa Dutka-Gianelli; Eric J. Nagid; Alexis A. Trotter; Kevin G. Johnson; Travis Tuten; James A. Whittington (Estuaries and Coasts, 2020)

Niche Partitioning Among Snook (Pisces: Centropomidae) in Rivers of Southeastern Florida and Implications for Species Range Limits - Philip W. Stevens; Jynessa Dutka-Gianelli; Eric J. Nagid; Alexis A. Trotter; Kevin G. Johnson; Travis Tuten; James A. Whittington (Estuaries and Coasts, 2020)

Did TV ads funded by fossil fuel industry defeat the Washington carbon tax? - Steven M. Karceski; Nives Dolšak; Aseem Prakash; Travis N. Ridout (Climatic Change, 2020)

Typha (Cattail) Invasion in North American Wetlands: Biology, Regional Problems, Impacts, Ecosystem Services, and Management - Sheel Bansal; Shane C. Lishawa; Sue Newman; Brian A. Tangen; Douglas Wilcox; Dennis Albert; Michael J. Anteau; Michael J. Chimney; Ryann L. Cressey; Edward DeKeyser; Kenneth J. Elgersma; Sarah A. Finkelstein; et al. (Wetlands, 2019)

Ocean Observations in Support of Studies and Forecasts of Tropical and Extratropical Cyclones - Ricardo Domingues; Akira Kuwano-Yoshida; Patricia Chardon-Maldonado; Robert E. Todd; George Halliwell; Hyun-Sook Kim; I.-I. Lin; Katsufumi Sato; Tomoko Narazaki; Lynn K. Shay; Travis Miles; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

Landscape patterns in top‐down control of decomposition: omnivory disrupts a tropical detrital‐based trophic cascade - Troy N. Simon; Andrew J. Binderup; Alex S. Flecker; James F. Gilliam; Michael C. Marshall; Steven A. Thomas; Joseph Travis; David N. Reznick; Catherine M. Pringle (Ecology, 2019)
Detrital‐based trophic cascades are often considered weak or absent in tropical stream ecosystems because of the prevalence of omnivorous macroconsumers and the dearth of leaf‐shredding insects. In this study, we isolate top‐down effects of three macroconsumer species on detrital processing in headwater streams draining Trinidad's northern mountains. We separated effects of different macroconsumers by experimentally manipulating their temporal access to isolated benthic habitat over the diel cycle. We found no evidence that omnivorous macroconsumers, including a freshwater crab ( Eudaniela garmani ) and guppy ( Poecilia reticulata ), increased leaf decomposition via consumption. By contrast, above a waterfall excluding guppies, the insectivorous killifish, Anablepsoides hartii , reduced the biomass of the leaf‐shredding insect Phylloicus hansoni 4‐fold, which consequently reduced leaf decomposition rates 1.6‐fold. This detrital cascade did not occur below the barrier waterfall, where omnivorous guppies join the assemblage and reduce killifish densities; here killifish had no significant effects on Phylloicus or decomposition rates. These patterns of detrital processing were also observed in upstream–downstream comparisons in a landscape study across paired reaches of six streams. Above waterfalls, where killifish were present, but guppies absent, leaf decomposition rates and Phylloicus biomass were 2.5‐ and ~35‐fold lower, respectively, compared to measurements below waterfalls. Moreover, the strength of top‐down control by killifish is reflected by the 20‐ and 5‐fold reductions in variability (± SE ) surrounding mean Phylloicus biomass and leaf decomposition rates in upstream relative to downstream reaches where no top‐down control was detected. Findings show a clear, detrital‐based trophic cascade among killifish, a leaf‐shredding insect, and leaf decomposition rates. Results also show how omnivorous guppies disrupt this cascade by depressing killifish densities, thereby releasing invertebrate shredders from predation, and significantly increasing decomposition rates. Moreover, this combination of direct and indirect trophic interactions drives patterns in decomposition rates in stream networks at a landscape scale, resulting in significantly lower rates of decomposition above vs. below barrier waterfalls. Our findings reveal that omnivory can result in significant indirect effects on a key ecosystem process, illustrating the importance of these hidden trophic pathways in detrital‐based systems and suggesting that resource control in tropical systems may be even more complex than previously envisioned.

Conducting and interpreting fish telemetry studies: considerations for researchers and resource managers - Jacob W. Brownscombe; Elodie J. I. Lédée; Graham D. Raby; Daniel P. Struthers; Lee F. G. Gutowsky; Vivian M. Nguyen; Nathan Young; Michael J. W. Stokesbury; Christopher M. Holbrook; Travis O. Brenden; Christopher S. Vandergoot; Karen J. Murchie; et al. (Reviews in Fish Biology and Fisheries, 2019)

Cotton (Gossypium hirsutum L.) mutants with reduced levels of palmitic acid (C16:0) in seed lipids - Corey N. Thompson; Bralie R. Hendon; Deepika Mishra; Jacob M. Rieff; Cindy C. Lowery; Kimberly C. Lambert; Travis W. Witt; Steven J. Oswalt; Efrem Bechere; C. Wayne Smith; Roy G. Cantrell; Brendan R. Kelly; et al. (Euphytica, 2019)

Influence of landscape heterogeneity on the functional connectivity of Allegheny woodrats (Neotoma magister) in Virginia - Jennifer M. Kanine; Elizabeth M. Kierepka; Steven B. Castleberry; Michael T. Mengak; Nathan P. Nibbelink; Travis C. Glenn (Conservation Genetics, 2018)

Functioning of Coastal River-Dominated Ecosystems and Implications for Oil Spill Response: From Observations to Mechanisms and Models - Adam Greer; Alan Shiller; Eileen Hofmann; Jerry Wiggert; Sally Warner; Sabrina Parra; Chudong Pan; Jeffrey Book; DongJoo Joung; Steven Dykstra; Jeffrey Krause; Brian Dzwonkowski; et al. (Oceanography, 2018)

Impacts of sea-level rise on sediment microbial community structure and function in two New England salt marshes, USA - Matt R. Simon; Gregory P. Zogg; Steven E. Travis (Journal of Soils and Sediments, 2017)

Chronic eccentric arm cycling improves maximum upper-body strength and power - Steven J. Elmer; Dakota J. Anderson; Travis R. Wakeham; Matthew A. Kilgas; John J. Durocher; Stan L. Lindstedt; Paul C. LaStayo (European Journal of Applied Physiology, 2017)

Autonomous and Lagrangian Ocean Observations for Atlantic Tropical Cyclone Studies and Forecasts - Gustavo Goni; Robert Todd; Steven Jayne; George Halliwell; Scott Glenn; Jili Dong; Ruth Curry; Ricardo Domingues; Francis Bringas; Luca Centurioni; Steven DiMarco; Travis Miles; et al. (Oceanography, 2017)

Emerging Opportunities for Landscape Ecological Modelling - Nicholas W. Synes; Calum Brown; Kevin Watts; Steven M. White; Mark A. Gilbert; Justin M. J. Travis (Current Landscape Ecology Reports, 2016)

A trait‐based approach for predicting species responses to environmental change from sparse data: how well might terrestrial mammals track climate change? - Luca Santini; Thomas Cornulier; James M. Bullock; Stephen C. F. Palmer; Steven M. White; Jenny A. Hodgson; Greta Bocedi; Justin M. J. Travis (Global Change Biology, 2016)
Estimating population spread rates across multiple species is vital for projecting biodiversity responses to climate change. A major challenge is to parameterise spread models for many species. We introduce an approach that addresses this challenge, coupling a trait‐based analysis with spatial population modelling to project spread rates for 15 000 virtual mammals with life histories that reflect those seen in the real world. Covariances among life‐history traits are estimated from an extensive terrestrial mammal data set using Bayesian inference. We elucidate the relative roles of different life‐history traits in driving modelled spread rates, demonstrating that any one alone will be a poor predictor. We also estimate that around 30% of mammal species have potential spread rates slower than the global mean velocity of climate change. This novel trait‐space‐demographic modelling approach has broad applicability for tackling many key ecological questions for which we have the models but are hindered by data availability.

A stochastic movement simulator improves estimates of landscape connectivity - A. Coulon; J. Aben; S. C. F. Palmer; V. M. Stevens; T. Callens; D. Strubbe; L. Lens; E. Matthysen; M. Baguette; J. M. J. Travis (Ecology, 2015)
Conservation actions often focus on restoration or creation of natural areas designed to facilitate the movements of organisms among populations. To be efficient, these actions need to be based on reliable estimates or predictions of landscape connectivity. While circuit theory and least‐cost paths (LCPs) are increasingly being used to estimate connectivity, these methods also have proven limitations. We compared their performance in predicting genetic connectivity with that of an alternative approach based on a simple, individual‐based “stochastic movement simulator” (SMS). SMS predicts dispersal of organisms using the same landscape representation as LCPs and circuit theory‐based estimates (i.e., a cost surface), while relaxing key LCP assumptions, namely individual omniscience of the landscape (by incorporating perceptual range) and the optimality of individual movements (by including stochasticity in simulated movements). The performance of the three estimators was assessed by the degree to which they correlated with genetic estimates of connectivity in two species with contrasting movement abilities (Cabanis's Greenbul, an Afrotropical forest bird species, and natterjack toad, an amphibian restricted to European sandy and heathland areas). For both species, the correlation between dispersal model and genetic data was substantially higher when SMS was used. Importantly, the results also demonstrate that the improvement gained by using SMS is robust both to variation in spatial resolution of the landscape and to uncertainty in the perceptual range model parameter. Integration of this individual‐based approach with other developing methods in the field of connectivity research, such as graph theory, can yield rapid progress towards more robust connectivity indices and more effective recommendations for land management.

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Genetic population structure of invasive nutria (Myocastor coypus) in Louisiana, USA: is it sufficient for the development of eradication units? - Karen Klima; Steven E. Travis (Biological Invasions, 2012)

Characterization of a genomic divergence island between black‐and‐yellow and gopher Sebastes rockfishes - VINCENT P. BUONACCORSI; SHAWN R. NARUM; KRISTINE A. KARKOSKA; STEVEN GREGORY; TRAVIS DEPTOLA; ALEXANDER B. WEIMER (Molecular Ecology, 2011)
Islands of high genomic divergence that contain genes of evolutionary significance may form between diverging species. The gopher rockfish, Sebastes carnatus, and black‐and‐yellow rockfish, S. chrysomelas , are sympatrically distributed temperate marine species inhabiting rocky reefs and kelp forests on the west coast of the United States. Prior studies documented low levels of genetic divergence between the two species, except at a single microsatellite locus that displayed high divergence, Sra .7‐2. To better characterize genome wide divergence, we scored 25 additional microsatellite loci. Mean neutral divergence between species ( F ST = 0.01) changed little from prior estimates. Sra .7‐2 continued to be an extreme divergence outlier. Five novel microsatellites within ± 15 kb of Sra .7‐2 were characterized. High divergence, consistently low diversity in S. chrysomelas , and linkage disequilibrium were detected at these loci, suggesting the influence of recent selection. However, coalescent modelling of divergence at neutral and Sra .7‐2 regions showed that initial divergence at Sra .7‐2 was ancient, likely predating divergence at neutral regions. It is therefore unlikely that Sra .7‐2 divergence represents solely recent ecological divergence within one species and may represent the action of recurrent selection. Introgressive gene flow (2 N E m ) was much higher (>>1) at neutral than Sra .7‐2 regions ( S. carnatus individuals have recently mixed ancestry at the Sra .7‐2 region. The Sra .7‐2 genomic region is likely one of several regions containing genes involved in initiating and maintaining species integrity. Completion of the final stages of speciation appears to be a slow and ongoing process for these species.

Clonal Structure of Invasive Cattail (Typhaceae) Stands in the Upper Midwest Region of the US - Steven E. Travis; Joy E. Marburger; Steve K. Windels; Barbora Kubátová (Wetlands, 2011)

Microsatellite markers isolated from the Mexican banded spring snail Mexipyrgus churinceanus - Lyndon M. Coghill; Johel Chaves-Campos; Flor E. Espinoza; Stacey L. Lance; Travis C. Glenn; Steven G. Johnson (Conservation Genetics Resources, 2011)

Red Mangrove Seedling Survival, Growth, and Reproduction: Effects of Environment and Maternal Genotype - Charles Edward Proffitt; Steven E. Travis (Estuaries and Coasts, 2010)

Successive bouts of cycling stimulates genes associated with mitochondrial biogenesis - Charles L. Dumke; J. Mark Davis; E. Angela Murphy; David C. Nieman; Martin D. Carmichael; John C. Quindry; N. Travis Triplett; Alan C. Utter; Sarah J. Gross Gowin; Dru A. Henson; Steven R. McAnulty; Lisa S. McAnulty (European Journal of Applied Physiology, 2009)

Disentangling the role of hybridization in the evolution of the endangered Arizona cliffrose (Purshia subintegra; Rosaceae): a molecular and morphological analysis - Steven E. Travis; Joanne E. Baggs; Joyce Maschinski (Conservation Genetics, 2008)

Rapid growth of a Eurasian haplotype of Phragmites australis in a restored brackish marsh in Louisiana, USA - Rebecca J. Howard; Steven E. Travis; Benjamin A. Sikes (Biological Invasions, 2008)

Red mangrove (Rhizophora mangle) reproduction and seedling colonization after hurricane charley: Comparisons of Charlotte Harbor and Tampa Bay - C. Edward Proffitt; Eric C. Milbrandt; Steven E. Travis (Estuaries and Coasts, 2006)

Resistance to apoptosis, increased growth potential, and altered gene expression in cells that survived genotoxic hexavalent chromium [Cr(VI)] exposure - Daryl E. Pritchard; Susan Ceryak; Keri E. Ramsey; Travis J. O'Brien; Linan Ha; Jamie L. Fornsaglio; Dietrich A. Stephan; Steven R. Patierno (Molecular and Cellular Biochemistry, 2005)

Nucleotide excision repair functions in the removal of chromium-induced DNA damage in mammalian cells - Travis J. O'Brien; Bradford R. Brooks; Steven R. Patierno (Molecular and Cellular Biochemistry, 2005)

Differential impact of ionic and coordinate covalent chromium (Cr)-DNA binding on DNA replication - Jamie L. Fornsaglio; Travis J. O'Brien; Steven R. Patierno (Molecular and Cellular Biochemistry, 2005)

Albino mutation rates in red mangroves (Rhizophora mangle L.) as a bioassay of contamination history in Tampa Bay, Florida, USA - C. Edward Proffitt; Steven E. Travis (Wetlands, 2005)

Mechanisms of chromium-induced suppression of RNA synthesis in cellular and cell-free systems: Relationship to RNA polymerase arrest - Jian Xu; Francis C.R. Manning; Travis J. O'Brien; Susan Ceryak; Steven R. Patierno (Molecular and Cellular Biochemistry, 2004)

Induction of pro-apoptotic and cell cycle-inhibiting genes in chromium (VI)-treated human lung fibroblasts: Lack of effect of ERK - Susan Ceryak; Carla Zingariello; Travis O'Brien; Steven R. Patierno (Molecular and Cellular Biochemistry, 2004)

Facilitation of survival and growth of Baccharis halimifolia L. by Spartina alterniflora Loisel. In a created Louisiana salt marsh - Jana Egerova; C. Edward Proffitt; Steven E. Travis (Wetlands, 2003)

Effects of glutathione on chromium‐induced DNA. Crosslinking and DNA polymerase arrest - Travis O'Brien; Jian Xu; Steven R. Patierno (Molecular and Cellular Biochemistry, 2001)